Analisis Perilaku Agresif Pada Siswa Remaja Sekolah Menengah Pertama - Monalisa Topayung; Amalia Wulandari; Putri Patrisia (PT. Citra Media Publishing, 2025)
Aggressive behavior among middle school students has become a significant concern for educators as it can disrupt the learning environment and impact students' social and emotional development. This study aims to analyze the factors influencing aggressive behavior among middle school adolescents, focusing on family, peer relationships, school environment, and social media. A descriptive qualitative approach was used through a literature review. The results indicate that internal factors such as frustration, psychological pressure, and family influences, along with external factors like peer relationships, social media, and the broader social environment, contribute to the emergence of aggressive behavior in students. This behavior can manifest as verbal actions, such as teasing and insults, as well as physical actions, such as fighting. Proposed prevention efforts include counseling services in schools and social skills training to increase students' awareness of the impacts of aggressive behavior. This research is expected to provide insights for educators and counselors in designing effective interventions to reduce aggressive behavior in the school environment.